The first year out : understanding American teens after high school - Clydesdale, Timothy T. (Timothy Thomas), 1965- (Morality and society., 2007)
Wild parties, late nights, and lots of sex, drugs, and alcohol. Many assume these are the things that define an American teenager?s first year after high school. But the reality is really quite different. As Tim Clydesdale reports in The First Year Out, teenagers generally manage the increased responsibilities of everyday life immediately after graduation effectively. But, like many good things, this comes at a cost. Tracking the daily lives of fifty young people making the transition to life after high school, Clydesdale reveals how teens settle into manageable patterns of substance use and s.